Efektivitas Pendidikan Kesehatan Oleh Bidan Dalam Meningkatkan Pemahaman Ibu Hamil Terhadap Buku Kia di Klinik Pratama Dharma Setia Husada Detasemen Kesehatan Paspampres Tahun 2024 - Ayu Resky Mustafa; Desy Murtini (Universitas Pahlawan Tuanku Tambusai, 2025)
The Maternal and Child Health (KIA) book plays an important role in increasing pregnant women's awareness of maternal health to reduce the Maternal Mortality Rate (MMR). Even though the MMR in Indonesia decreased from 390 (1991) to 189 (2020) per 100,000 live births, accelerated efforts are still needed to achieve the 2030 SDGs target of 70 per 100,000 live births. In DKI Jakarta, the 2023 MMR will reach 43.5 per 100,000, lower than the SDGs target. However, the use of the KIA Book is not optimal because it is still considered just an inspection record. Education has been proven to increase mothers' understanding, as previous research showed an increase in knowledge from 13.3% to 91.9% after socialization. Obstacles such as limited health worker education and examination time need to be overcome through effective educational strategies to improve maternal and child health and reduce MMR.To determine the effectiveness of health education conducted by midwives in improving pregnant women’s understanding of the mother and child health (MCH) book.Quantitative approach, utilizing a quasi-experimental design with a one-group pretest-posttest without a control group.Based on bivariate analysis using the Paired T-Test, the results showed a significant value of 0.000 (p < 0.05). Thus, the alternative hypothesis (Ha) was accepted, and the null hypothesis (H0) was rejected. It can be concluded that health education provided by midwives significantly improves pregnant women's understanding of the MCH book. Health education interventions are effective in increasing pregnant women's knowledge or understanding regarding maternal and child health information in the KIA book.